Pembuatan E-Modul Usaha dan Energi Berbasis Pemecahan Masalah - Lestari, Rini; Derlina, Derlina; Juliani, Rita; Bukit, Nurdin; Hakim, Abd.; Sahyar, Sahyar (IPM2KPE, 2024)
This study aims to determine the validity of the design and results of the design of e-modules. problem solving based on business and energy. This study is the creation of electronic modules of business and energy based on problem solving validated by 1 media expert to evaluate the appearance and suitability of the module, then 1 Theory expert to evaluate the depth of the content of the e-module designed by Lecturers at the State University of Medan. The instruments used in this study were questionnaires, media expert validation and material expert questionnaire validation. The results obtained from the aspect of the designed validity of the input of media experts obtained an average score of 88.3% in the very feasible category and for the evaluation of Theory experts the average value was 90.5% in the very feasible category. Based on the results of the study, it was concluded that the e-module of business and energy based on problem solving was valid. Keywords: E-Business Module, Energy, Problem Solving